RELIGI JAWA DAN REMAKING TRADISI GREBEG KRATON, SEBUAH KAJIAN ANTROPOLOGI - Brata, Nugroho (Jurnal Sejarah dan Budaya, 2009)
Abstract: One of traditions still maintained by Yogyakarta society is grebeg kraton. Issues appointed in this paper are; first, how does Javanese society interpret phenomenon of grebeg Kraton Yogyakarta in the present time? Second, can remaking of a tradition be conducted so that it is able to create a new tradition? Method used in this research was qualitative research method. Data collection was conducted using observation technique, observation participatory, and depth interview.The discussion results showed; first, that in the present time which has been considered as modern age there are apparently Javanese society who still believes the existence of Kingâs blessing through goods media in form of Grebeg Mountains. Second, grebeg mountains tradition, in fact, can be reproduced or remade by Kraton Yogyakarta (Yogyakarta Palace) and society who hold mass movement pisowanan ageng on May 20, 1998 to demand Soeharto the President to retreat. The society who came in groups to Sultan in Alun-alun Lor Kraton Yogyakarta (North Square of Yogyakarta Palace) got foods and drinks freely in road banks toward the Palace. The model of grebeg mountains was remade become Sultanâs appeal to the society around the roads passed by mass of pisowanan ageng in order the society provides free foods and drinks to the mass.